PENGARUH PROMOSI DAN STORE ATMOSPHERE TERHADAP MINAT BELI KONSUMEN SELEBRITI PADA ASIAN&SUKI RESTAURANT PEKANBARU - Rahma Puspita Sari; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The research conducted at Selebriti Asian&Suki Restaurant Pekanbaru where located in Jl. Sudirman No.426 Lt 1, Gedung Star City Square. The problem in this study is number of buyers has decreasing, percentage of target achievement has decreased, and the failure of the company’s sales target has not been achieved, this study aims to determine the effect of promotion and store atmosphere on customer purchase intention Selebriti Asian&Suki Restaurant Pekanbaru . In this study use quantitive descriptive with SPSS program. The population in this is are consumers at Selebriti Asian&Suki Restaurant. The sampling technique chosen is slovin Formula with a sample 97 respondents. Hypothesis testing uses a simple linear analysis method and multiple analysis with result showing that promotion and store atmosphere have a positive and significan on customer purchase intention Selebriti Asian&Suki Restaurant. With the calculation of the coefficient of determination (R2) promotion on customer purchase intention of R square is 0,510 or 51% and store atmosphere on purchase intention the value of R square is 0,407or 40,7% and coefficient of determination (R2) promotion and store atmosphere the value of R square is 0,625 or 62,5%. This show that the promotion and store atmosphere gives an effect of 37,5% on purchase intention at Selebriti Asian&Suki Restaurant, while remaining 37,5% is effected by other variables that are not examined in this study. Keywords : Promotion, Store Atmosphere,Customer Purchase Intetion